PENDIDIKAN SOSIAL KEMASYARAKATAN DALAM PERSPEKTIF AL-QUR'AN DAN HADITS - Ali Akbar (CV. Adiba Aisha Amira, 2021)
The value of social education taught in the Qur'an and al-Hadith is very much, including the values of brotherhood, helping, caring, forgiving, tolerant, giving each other, not being individualistic, giving each other and giving spaciousness to others. Actually, there are many more values of social education that are described in the Qur'an and al-Hadith, due to limitations, several examples of the value of social education are taken which are informed in the Qur'an and al-Hadith. Social education in Islam educates its people to get used to carrying out good social etiquette and noble psychic basics and sourced from the eternal Islamic faith and deep feelings of faith, so that in society they can appear with good association and manners, balance of mind that is good. mature and wise action. Islamic education is an effort to develop, encourage and invite students to live more dynamically based on high values and a noble life. With this process, it is hoped that a more perfect student personality will be formed, both related to the potential of reason, feelings, and actions